PEMAKNAAN ORNAMEN MURDHA PADA ARSITEKTUR TRADISIONAL BALI - I Nyoman Widya Paramadhyaksa (INFO-TEKNIK, 2009)
Murdha is an ornament lain on the top of Balinese traditional buildings which are generally functioned for religious and spiritual activities. This article discusses about the interpretation of symbolic meaning of murdha ornament. The method applied in this study is hermeneutic and using some approaches, such as: formal approach, religion concept approach, mythology, community belief, and comparison with other ornaments which have similar values with murdha. The finding shows that murdha is closely related to heaven as the final destination of the human’s soul after his death on earth.